Liquid Crystal Templated Chiral Plasmonic Films with Dynamic Tunability and Moldability. (9th January 2022) - Grzelak, Dorota; Tupikowska, Martyna; Vila‐Liarte, David; Beutel, Dominik; Bagiński, Maciej; Parzyszek, Sylwia; Góra, Monika; Rockstuhl, Carsten; Liz‐Marzán, Luis M.; Lewandowski, Wiktor
Abstract: Thin films sustaining plasmonic circular dichroism (PCD) have acquired high scientific relevance and a great potential for applications. While most efforts in PCD thin film structures focus on lithographically fabricated static metasurfaces, the bottom‐up fabrication of active chiral plasmonic films constitutes an alternative approach. Herein, the preparation of PCD thin films by melting and freezing a mixture of liquid crystal (LC), a chiral dopant, and gold nanoparticles (Au NPs), serving as helical matrix, symmetry breaking inducer, and plasmonic component, respectively is reported. UV–vis and circular dichroism spectroscopies, as well as theoretical modeling are used to disclose the interactions among thin film components, toward maximizing the PCD dissymmetry factor (g‐factor). Variation of substrate temperature affords reversible off/on switching of the chiroptical response. The soft nature of LC matrix enables patterning of the films via a thermal nanoimprinting method, using a polydimethylsiloxane mold for transfer‐printing onto a flexible substrate, leading to stretchable PCD films. The PCD wavelengths can be readily tuned by varying the geometry of the Au NPs. This work provides an efficient technique to produce PCD thin films with active plasmonic properties and mechanical tunability. Abstract : Chiral plasmonic thin films can be prepared by using liquid crystals as hosts for Au nanoparticles. This versatile fabrication concept relies on the dynamic tunability of liquid crystals and leads to customized assemblies with responsive chiroptical properties. The soft character of the film enables transfer to flexible substrates and imprinting, affording stretchable and nanopatterned chiral plasmonic films.